Autopsy: a value to primordial and primary prevention for lung diseases - Rana, Deepshikha; Kaushik, Nidhi; Verma, Renuka; Pawar, Richa; Lamba, Ekta; Sen, Rajeev (International Journal of Research in Medical Sciences, 2022)
Background: Lung disorders spectrums include congestion, oedema, various inflammatory lesions, chronic obstructive pulmonary diseases and neoplastic lesions. The clinical and radiological findings in respiratory diseases are nonspecific and therefore a histopathological study is essential. Autopsies are necessary to establish cause of death of the person with help of antemortem history and investigations to rule out lung lesions. Aims and objectives were to identify the histopathological spectrum of lung disease and frequency of various lung pathologies in respect to age and sex. Methods: The retrospective study of 285 lung autopsy specimens received were fixed and processed. Routine paraffin sectioning was done followed by hematoxylene and eosin (H and E) staining. Relevant clinical and postmortem findings, gross and microscopic examination findings were recorded. Results: Most common lung pathology found was Edema and congestion in 149 cases (52.2%), pneumonia in 87 cases (30.5%) followed by tuberculosis in 33 cases (11.5%). Out of total 285 cases, 222 (77.9%) were males and 63 cases (22.2%) were females. The male to female ratio was 3.5:1. Maximum numbers of cases, in age group of 31-45 years were 108 cases (37.89%) followed by in age group 46-60 years were 90 cases (31.57%) followed by age group of 16-30 years 15.8%. Conclusions: Advances in diagnostic technology have not reduced the value of autopsy for the study and evaluation of the disease process. It has become crucial for adopting correct prophylactic actions for primordial and primary prevention of pulmonary dysfunctions.